Risk factors and nomogram prediction model for recurrence after radiofrequency ablation in patients with persistent atrial fibrillation - Shu-Cai Zhao; Hao Guo; Da-Zhou Lei (BMC Cardiovascular Disorders)
Abstract Background Recurrence of atrial fibrillation (AF) after radiofrequency catheter ablation (RFA) remains a major clinical challenge in patients with persistent AF. This study aimed to identify independent risk factors for post-ablation recurrence and to develop a nomogram prediction model integrating clinical, laboratory, and echocardiographic parameters. Methods In this retrospective study, 306 patients with persistent AF who underwent first-time RFA between June 2021 and June 2024 were enrolled. Patients were stratified into recurrence (n = 96) and non‐recurrence (n = 210) groups based on documented AF episodes during six-month follow-up. Preprocedural assessments encompassed three main domains: electrophysiological evaluations, echocardiographic measurements, and serum biomarkers. Multivariate logistic regression identified independent predictors of recurrence. A nomogram was constructed and internally validated using bootstrap resampling. Predictive performance was assessed by area under the receiver operating characteristic curve (AUC), calibration analysis, and decision curve analysis (DCA). Results Elevated left atrial volume index (LAVI), reduced left atrial appendage emptying velocity (LAAEV), reduced left atrial appendage ejection fraction (LAAEF), elevated brain natriuretic peptide (BNP), and elevated neutrophil-to-lymphocyte ratio (NLR) emerged as independent predictors of AF recurrence (all P < 0.05). The nomogram achieved an AUC of 0.893 (95% CI, 0.826–0.968), with sensitivity of 85.7% and specificity of 91.3%. Internal validation yielded a concordance index of 0.783 (95% CI, 0.722–0.869), and the Hosmer–Lemeshow test indicated good calibration (P = 0.851). DCA demonstrated a favorable net benefit across a range of threshold probabilities. Conclusions A nomogram incorporating LAVI, LAAEV, LAAEF, BNP, and NLR provides accurate individualized risk estimates for AF recurrence following RFA in persistent AF patients and may guide tailored clinical management.